1991
DOI: 10.1111/j.1699-0463.1991.tb01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessels in human immunodeficiency virus‐related lymphadenopathy: high endothelial venules and lymphocyte migration

Abstract: Csanaky G., Pap, T., Kalasz, V., Kelenyi, G. Blood vessels in human immunodeficiency virus-related lymphadenopathy: high endothelial venules and lymphocyte migration. APMIS 99: 640-644, 1991.The vasculature of 25 lymph nodes of patients with human immunodeficiency virus-related lymphadenopathy was investigated morphometrically. The number of small vessels, the morphological features of high endothelial venules and the migratory index of the lymphocytes passing through the high endothelial venules, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…These results indicated that the increased input of naïve lymphocytes to the dLN is at least in part mediated by a rapid increase in the number of HEVs. We reasoned that the increase in lymphocyte recruitment through additional HEVs must be achieved by an increase in blood supply into the LNs, as suggested by previous studies in larger animals (24,29,30). If so, the arteriole feeding the dLN must expand to accommodate an increase in blood flow.…”
Section: Mechanism Of Inflammation-induced Recirculationmentioning
confidence: 85%
“…These results indicated that the increased input of naïve lymphocytes to the dLN is at least in part mediated by a rapid increase in the number of HEVs. We reasoned that the increase in lymphocyte recruitment through additional HEVs must be achieved by an increase in blood supply into the LNs, as suggested by previous studies in larger animals (24,29,30). If so, the arteriole feeding the dLN must expand to accommodate an increase in blood flow.…”
Section: Mechanism Of Inflammation-induced Recirculationmentioning
confidence: 85%